Implementasi Model Pembelajaran Kelas Terbalik pada Pembelajaran Pendidikan Agama Islam di Sekolah Dasar Islam Terpadu - Edi Nurhidin (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2022)
This study describes applying the flipped classroom learning model to Islamic religious education (PAI) subjects at the Darul Abidin Integrated Islamic Primary School, Depok. This study uses a descriptive qualitative research type. The study results indicate that the PAI learning process with the flipped classroom learning model has been integrated with the learning characteristics of the Integrated Islamic School Network (JSIT), namely 'integrated' learning. The learning activities are divided into two forms, namely independent learning at home and learning in class, both virtual-zoom categories and limited face-to-face meeting classes. The support system for learning activities is quite diverse, consisting of the availability of e-learning, the use of various platforms such as Zoom Meetings and Quizizz, and the use of different learning resources such as interactive learning videos and subject matter in the form of powerpoint, and textbooks. ABSTRAK Kajian ini bertujuan untuk mendeskripsikan penerapan model pembelajaran kelas terbalik pada mata pelajaran pendidikan agama Islam (PAI) di Sekolah Dasar Islam Terpadu Darul Abidin Depok. Kajian ini mengggunakan jenis penelitian kualitatif deskriptif. Hasil penelitian menunjukkan bahwa proses pembelajaran PAI dengan model pembelajaran kelas terbalik telah terintegrasi dengan karakteristik pembelajaran jaringan sekolah Islam terpadu (JSIT), yakni pembelajaran ‘terpadu’. Aktivitas pembelajaran yang terbangun terbagi menjadi dua bentuk yaitu pembelajaran mandiri di rumah dan pembelajaran di kelas baik kelas virtual-zoom maupun kelas pertemuan tatap muka terbatas. Sistem pendukung aktivitas pembelajaran cukup beragam yang terdiri dari ketersediaan e-learning, pemanfaatan beragam platform seperti zoom meeting dan quizizz, serta pemanfaatan beragam sumber belajar seperti video pembelajaran interaktif, materi pelajaran dalam bentuk powerpoint, dan buku teks.